AND MISSION AND STUDENTS' ACADEMIC ACHIEVEMENT - Bahaudin; Andriani Sariwardani; Ratna Dewi (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2025)
This study aims to examine the relationship between the principal's role in implementing the school's vision and mission and students' academic achievement. The principal plays a strategic role in guiding and building a school culture that supports student success, particularly through a clear and consistently applied vision and mission. This research uses a quantitative approach with a correlational method. Data were collected through observations, interviews, and questionnaires administered to teachers and staff at SDN Linduk 1, along with documentation of students’ academic scores as indicators of academic achievement. The results of the study show a significant positive relationship between the implementation of the vision and mission by the principal and the improvement of students' academic performance. These findings indicate that principal leadership oriented toward a clear vision and mission can have a positive impact on the quality of education in elementary schools.